An analysis of maslahah's development through al-Ghazali pre and post al-Ghazali periods - Laluddin, Hayatullah; Mohammad, Mohamad Nasran; Mohd. Kusrin, Zuliza; Ahmad, Shofian; Nasoha, Zaini; Muda , Mohd. Zamro; Ahmad, Md. Yazid; Husni, Ahmad Muhammad (Medwell Journals, 2012)
The purpose of this article is to expose and identify the development of maslahah, as a dynamic principle of the Islamic jurisprudence of a high methodological significance. To achieve this objective, the authors undertake an in depth study of jurists discourse on maslahah, and hence, an analysis of the various stages of its development. Both historical and analytical methods are adopted in this article. The authors by referring to Muslim jurists’ discourse on maslahah, in the context of the development of legal theory, derive the conclusion, that maslahah initially was perceived as a notion of consideration of public welfare. However, its use in this sense was on ad hoc basis and lacked consistency. Its elaborate discussion and hence, recognition as a mature technical term materialised during the fifth century of hijrah. This can be observed clearly from the writings of Muslims jurists of pre-al-Ghazali, during al-Ghazali and post-al-Ghazali periods including those of al-Ghazali’s writings, himself. However, Al-Shātibī discussion of maslahah within the framework of the theory of the purposes of the law, made it of remarkable and profound importance to methodological reconstruction and renewal of Islamic law.